PENDIDIKAN BERPAKAIAN DALAM PERSPEKTIF AL-QUR’AN - Harmonedi Harmonedi; Zul Atiqah; Hubban Jamma (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The flow of globalization has penetrated various lines of life, including how to dress. New trends in clothing also continue to experience developments and changes. Dress styles that are open and accentuate the curves of the body so that a fashionable Muslim fashion style becomes stylish and trendy on the grounds that she has an attractive appearance. This style of dress has penetrated various levels of society, including Muslims. Departing from this problem, a library research was carried out by placing four tafsir books, as well as several other literatures as sources. Based on the research results, it turns out that from a long time ago the Qur'an has educated people about the ideal dress code. al-Qur'an educates people clearly and decisively to dress according to the type, context, and ethics that are correct according to Islamic law. All of this is in line with the essential purpose of dressing, namely maintaining honor, dignity, and avoiding human beings from slander and sin.